Product Development Strategy Of Durian Peresak Fruit Nature Tourism In West Lombok Regency West Nusa Tenggara - Widiantara, I Gusti Agung Bagus; Dwi Poetranto, Isa Wahjoedi; Budiasa, I Ketut (Akademi Komunitas MAPINDO, 2024)
Indonesia has extraordinary tourism potential which consists of natural, cultural and artificial potential and isspread throughout the archipelago, Natural potential is flora or plants from which leaves, wood, fruit, flowers,and root oil are taken and processed into bio briquettes. Plants in Indonesia come from native Indonesia andsome plants came from other countries during the colonial period as export commodities with high economicvalue, such as spices, tea, coffee, vanilla, and so on. The existence of this plant is even able to attract the attentionof other nations to come to Indonesia. The spread of this plant starts from western to eastern IndonesiaOne of the Indonesian islands is Lombok Island in West Nusa Tenggara Province. Tourism on Lombok Island isincreasingly developing in line with government policies and the increasing number of investors who invest inof the tourism sector. Growth of tourism on this island is growing because the natural conditions of LombokIsland are suitable for the growth of various unique flora including the peresak durian that has been recognizedby many parties as having potential and superiority, unfortunately, the income from selling Peresak Durian isstill limited so it only serves as additional income for residents when the harvest season arrives. It is necessaryto think about a development strategy using using SWOT an analysis that describes the strength, a weakness,an opportunity, and a threat.Keywords: Development Strategy, Durian Peresak, Natural Tourism Products, SWOT Analysis.